Prevalence of Dental Enamel Hypoplasia in the Neolithic Site of Wadi Shu'eib in Jordan - Salah El-; Issa Sarie' (Dental Anthropology Association, 1997)
A study of Neolithic Pre-Pottery B materials from Wado Shu'eib revealed that 38.40% of the examined teeth have dental enamel hypoplasia (DEH). Sixty percent of the anterior teeth exhibit DEH while only 21.40% of the posterior have the defect. The most affected teeth are the maxillary central incisors (72.73%) and the lower canines (62.5%). The most prevalent type of defect is the groove which is present in 68.75% of the teeth with DEH. One notable case is a lateral incisor with a slight deep and sharp groove. The sharpness and the deepness of this groove may indicate a severe stress which caused DEH to occur in a very short period. The most likely causes of DEH were general nutritional stresses. Another cause may have been environmental stresses.